Design of a pneumatic muscle based continuum robot with embedded tendons - Kang, Rongjie; Guo, Yong; Chen, Lisha; Branson, David T.; Dai, Jian S. (Institute of Electrical and Electronics Engineers, 2016)
Continuum robots have attracted increasing focus in recent years due to their intrinsic compliance that allows for dexterous and safe movements. However, the inherent compliance in such systems reduces the structural stiffness, and therefore leads to the issue of reduced positioning accuracy. This paper presents the design of a continuum robot employing tendon embedded pneumatic muscles (TEPMs). The pneumatic muscles are used to achieve large scale movements for preliminary positioning while the tendons are used for fine adjustment of position. Such hybrid actuation offers the potential to improve the accuracy of the robotic system, while maintaining large displacement capabilities. A 3-dimensional (3-D) dynamic model of the robot is presented using a mass-damper-spring based network, in which elastic deformation, actuating forces and external forces are taken into account. The design and dynamic model of the robot are then validated experimentally with the help of an electromagnetic tracking system.